IMPROVING STUDENTS’ ABILITY IN WRITING AN ESSAY THROUGH PEER-ASSESSMENT STRATEGY AT THE FIFTH SEMESTER IN CIPTA WACANA CHRISTIAN UNIVERSITY OF MALANG - misianto misianto (JURNAL ILMIAH BAHASA DAN SASTRA, 2014)
Abstract: English students are expected to be able to produce an effective essay for the sake of their academic writing. For this purpose, they should pay attention to the rhetorical aspects of writing such as content, organization of ideas, discourse, syntax, vocabulary, and mechanics. This article presents the result of classroom action research conducted to overcome practical problems of writing an essay by using peer-assessment strategy. The subject of this study was 14 fifth-semester students of CiptaWacanaChristianUniversity of Malang taking essay writing class. In general the strategy proves effective in improving the students’ ability in writing an essay. In addition to the writing achievement, the strategy is able to improve the quality of learning process of essay writing. The students are motivated to write an essay more enthusiastically and are much aided to be a better writer; they no more think that writing is a burden, so they have a good response and an attitude to the strategy.